On the Uses of Decolonial History for Life - Volodymyr Sklokin (Вивліоѳика)
This essay provides arguments in favor of decolonizing the field of Russian and East European Studies, focusing on the eighteenth-century history of Ukrainian-Russian relations. It envisages two directions for decolonization: overcoming the traditional narrative of Russian history and rethinking the basic categories we use to tell the history of the Russian Empire. It argues that we should reconsider a one-sided view of empire as an embodiment of the politics of difference and pay more attention to the early modern policies of acculturation and assimilation that took the form of russification in the Russian Empire. It also emphasizes the need to overcome reductionism, typical of traditional national history. The history of the Ukrainian-Russian encounter in the early modern period cannot be presented as a black-and-white narrative of Russian subjugation and repression and Ukrainian resistance. It was a more complex story that also included a dimension of cultural entanglement with strong mutual influences.